2021
DOI: 10.3389/fnmol.2021.753537
|View full text |Cite
|
Sign up to set email alerts
|

Altering Cell-Cell Interaction in Prenatal Alcohol Exposure Models: Insight on Cell-Adhesion Molecules During Brain Development

Abstract: Alcohol exposure during pregnancy disrupts the development of the brain and produces long lasting behavioral and cognitive impairments collectively known as Fetal Alcohol Spectrum Disorders (FASDs). FASDs are characterized by alterations in learning, working memory, social behavior and executive function. A large body of literature using preclinical prenatal alcohol exposure models reports alcohol-induced changes in architecture and activity in specific brain regions affecting cognition. While multiple putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 250 publications
(270 reference statements)
3
4
0
Order By: Relevance
“…In all of these, multiple categories were identified through differing analyses, strengthening their association in this study. The further validation of cell adhesion as responding to PAE once more serves to validate our study [46]. Our work supports these conclusions and furthermore indicates that they persist long after initial alcohol exposure, continuing into adolescence.…”
Section: Plos Onesupporting
confidence: 85%
See 2 more Smart Citations
“…In all of these, multiple categories were identified through differing analyses, strengthening their association in this study. The further validation of cell adhesion as responding to PAE once more serves to validate our study [46]. Our work supports these conclusions and furthermore indicates that they persist long after initial alcohol exposure, continuing into adolescence.…”
Section: Plos Onesupporting
confidence: 85%
“…This is complemented by other cell adhesion genes that are upregulated in response to ethanol exposure, such as TCAM1 . The identification of cell adhesion in particular serves to validate our study, as previous work has demonstrated that PAE can alter cell-cell interactions through changes in cadherin expression during development [ 46 ]. Changes in expression of these genes suggest that prenatal ethanol exposure may lead to changes in neuronal connectivity that persist well past fetal development into adolescence.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, alcohol can also influence the kinases that influence the CAMs functions [13]. These CAM-mediated activities are vital for the growth of the embryo, fetus, and newborn, resulting in developmental and behavioral abnormalities after birth, and could play a role in the development of FASD [11,14].…”
Section: Biochemical Mechanisms That Influence Fasdmentioning
confidence: 99%
“…Physical development may be impacted by prenatal alcohol exposure, and postnatal adversity resulting in a growth impairment in height, weight, and head circumference. A growth deficiency is commonly identified when age-gender height and weight fall below the tenth percentile [14]. Growth delays increase a child's overall health risks by affecting their general health and cognitive and physical development.…”
Section: Growth Deficiencymentioning
confidence: 99%